The Effect of Profitability and Liquidity on Firm Value with Dividend Policy as an Intervening Variable (Empirical Study on Non-Cyclical Consumer Sector Companies Listed on the Indonesia Stock Exchange Period 2018-2023) - MARCHELINA, Della; SANUSI, Fauji; PURBASARI, Intan (Journal of Governance, Taxation and Auditing, 2025)
This study aims to determine the effect of Profitability and Liquidity on Firm Value with Dividend Policy as an Intervening Variable in Consumer Non-Cyclicals Sector Companies listed on the Indonesia Stock Exchange for the 2018-2023 period. The sampling technique employed a purposive sampling method, aiming to obtain sample data by the study's criteria, and resulted in the selection of 24 companies from a population of 70 companies. The data analysis techniques employed in this study include descriptive statistics, classical assumption tests, and Sobel tests, utilizing SPSS 25 software. The results of this study indicate that: (1) Profitability has a positive significant effect on Firm Value, (2) Liquidity has a negative significant on Firm Value, (3) Dividend Policy has a positive significant effect on Firm Value, (4) Profitability has a positive significant effect on Dividend Policy, (5) Liquidity does not affect on Dividend Policy, (6) Dividend Policy can mediate the effect of Profitability on Firm Value, (7) Dividend Policy is unable to mediate the effect of Liquidity on Firm Value.